Model of management of teacher accompaniment in online and distance education programs - Rodríguez Hernández, Ariel Adolfo; Universidad Pedagógica y Tecnológica de Colombia; Pinzón Villamil, Josué Nicolás; Universidad Pedagógica y Tecnológica de Colombia; Avella Forero, Fanny; Universidad Pedagógica y Tecnológica de Colombia; Moreno Cely, Claudia Patricia; Universidad Pedagógica y Tecnológica de Colombia; Camacho, Mauricio Enrique; University of Applied Sciences and Arts; Rodríguez Niño, María Consuelo; Universidad Nacional Abierta y a Distancia (UPTC Editorial, 2022)
The book presents the results of the research that aimed to design a quality management model for teacher support in distance and online education programs, taking the Pedagogical and Technological University of Colombia as a case study in order to improve and follow up the process. In chapter 1, the methodology used, the problem situation and the methodological design developed for the research approach are exposed. Chapter 2 presents the theoretical and conceptual bases that support the teaching tutorial accompaniment. Chapter 3 delivers the results of the research in each of its phases and that lead to the management model of teacher support proposed for distance and online education programs. The definitions, architecture, pedagogical and support strategies, management and monitoring of the same are shown. Finally, in chapter 4, the integration of the teacher support model, the concept and scope of educational technological competence of the teacher in distance and online education is made. As a closing, some technologies and digital tools that can support the teaching accompaniment processes are delivered as a suggestion.